Integrated Crop Management Practices Improve Grain Yield and Resource Use Efficiency of Super Hybrid Rice - Deng, Jun; Harrison, Matthew Tom; Liu, Ke; Ye, Jiayu; Xiong, Xin; Fahad, Shah; Huang, Liying; Tian, Xiaohai; Zhang, Yunbo (Frontiers in Plant Science, 2022)
Super hybrid rice genotypes have transformed the rate of genetic yield gain primarily due to inter-subspecific heterosis, although the physiological basis underpinning this yield transformation have not been well quantified. Here, we assessed the radiation-use efficiency (RUE) and nitrogen-use efficiency (NUE) of novel hybrid rice genotypes under four management practices representative of rice cropping systems in China. ‘Y-liangyou 900’ (hereafter, YLY900) - a new super hybrid rice widely adopted in China - was examined in field experiments conducted in Jingzhou and Suizhou, Hubei Province, China, from 2017 to 2020. Four management systems were conducted: nil fertilizer (CK), conventional farmer practice (FP), high yield high efficiency (HYHE) and super high yield (SHY). Yield differences across the treatment regime were significant (p<0.05). Yields of the SHY treatment in Jingzhou and Suizhou were 11 t ha-1 and 12 t ha-1, some 14% and 27% greater than yields obtained in the HYHE and FP treatments, respectively. Relative to the HYHE and FP treatments, SHY had greater panicle numbers (9%, 18%), spikelets per panicle (7%, 12%), spikelets per unit area (17%, 32%) and total dry weight (9%, 19%). Average RUE of SHY was 2.7 g MJ-1, a value 5% and 9% greater than that observed for HYHE and FP respectively due to higher intercepted photosynthetically active radiation (IPAR) in the former treatment. The efficiency of nitrogen fertilizer uptake (AEN) of SHY was 17 kg N kg-1 grain, 9% and 68% higher than that measured for HYHE and FP. For the SHY treatment, we elicit tight correlations between yield and both panicle number (R2 = 0.91) and spikelets per panicle (R2= 0.83). We conclude that SHY grain yields are associated with greater light interception, IPAR, RUE and total dry matter. We suggest that integrated management practices are conducive to higher resource use efficiency and grain yield through expansion of sink potential via increased panicle numbers and spikelets per panicle.